Metal sulfides: photoluminescence and photocatalytic properties - Ratmann, Cristiane Wienke Raubach (2013)
In this work we report an experimental and theoretical study of photoluminescence (PL) and photocatalytic activity of pure metal sulfides and systems furnished prepared by microwave assisted solvothermal (MAS) method. The theoretical model of the decorated system was created in order to analyze the electronic transition, especially in their interfaces. The results show that the system interface decorated (core-shell) produces an electron charge transfer of holes from cadmium sulfide (CdS) to zinc sulfide (ZnS), which helps increase the PL and photocatalytic activity of the system. For the pure systems, was observed the efficacy of the method synthesis employed verified that the process for obtaining the ZnS and calcium sulfide (CaS) was extremely important. Through the theoretical models was possible to evaluate the influence caused by the solvothermal influence caused by the MAS method. The variation in the synthesis parameters shows a direct influence on the PL properties of sulfides obtained which can be attributed to structural organization. The theoretical results how this order and disorder of the system can affect these properties of the obtained materials.